Determinants of MSME Financing in OJK-Listed Regional Development Banks: An Islamic Perspective on Interest Rate as a Moderating Variable - Fany, Firyal Afria; Utami, Yuni; Amirah, Amirah (IJIBE (International Journal of Islamic Business Ethics), 2025)
This study aims to analyze the influence of third-party funds, non-performing loans, return on assets, and capital adequacy ratio on MSME financing distribution with interest rates as a moderating variable at regional development banks (RDBs) registered with the OJK (Financial Services Authority of Indonesia) during the 2020–2024 period. The research uses 115 samples from a population of 23 companies, selected using purposive sampling. This study employs quantitative data obtained from published financial statements of the OJK for 2020-2024. The analytical methods used are multiple linear and moderated analyses (MRA), processed using SPSS software. The study shows that third-party funds, return on assets, and capital adequacy ratio positively and significantly affect MSME financing. In contrast, non-performing loans have no significant impact. Interest rates significantly moderate the relationships between third-party funds, non-performing loans, and capital adequacy ratios with MSME financing. Conversely, they do not exhibit moderation on the relationship between ROA and MSME financing.